Peran Sekretariat Badan dalam Pengelolaan Keuangan dan Aset Daerah: Sekretariat Bkad Kota Medan - Astri Sri Rezeki Harahap; Yusrizal (Masyarakat Ekonomi Syariah Bogor, 2024)
The purpose of this study is to find out what the role of the agency secretariat is in the management of regional finances and assets. In this study, the author uses a qualitative method with a descriptive approach. The BKAD Secretariat can be interpreted as a supporting unit that provides administrative and technical services to all parts of BKAD. The results of this study show that the Secretariat of the Regional Financial and Asset Management Agency (BKAD) plays a role as a unit responsible for coordinating and implementing regional financial and asset management policies. This role includes budgeting, supervising fund allocation, and managing and maintaining regional assets. The effectiveness of the BKAD Secretariat is very important in ensuring that the management of regional finances and assets is carried out appropriately, in accordance with laws and regulations, and transparently. In addition, the importance of communication between teams in every implementation of various activities or work of an organization.